The Bluebook : A Uniform System of Citation - The Columbia Law Review; The University of Pennsylvania Law Review (Cambridge, Massachusetts : The Harvard Law Review Association, 2015)
This edition of The Bluebook retains the same basic approach to legal citation established by its predecessors. The layout of the Bluebook has been updated to make the information easier to access
Includes bibliographical references and index
Keywords: Citation of legal authorities -- United States; Annotations and citations (Law) -- United States